Fables. [02], Animal farm - Willingham, Bill (Fables, 2003)
Travel to upstate New York, where the non-human Fable characters have found refuge on a farm, miles from mankind. But all is not well on the farm <U+2014> and a conspiracy to free them from the shackles of their perceived imprisonment may lead to a war that could wrest control of the Fables community away from Snow White. Starring Goldilocks and the Three Bears. Plus, a sketchbook section featuring art by Willingham, Buckingham and Jean.